Estimativa de massa livre de gordura em pacientes com distrofia muscular de Duchenne e efeito da suplementação com zinco sobre parâmetros ósseos dessa população - Grilo, Evellyn Câmara (2021)
Duchenne Muscular Dystrophy (DMD) is a neuromuscular disease that results in progressive muscle atrophy. For the DMD population, body composition assessment and bone health management are important. Given these health demands of the population with DMD, this doctoral thesis had as main objectives: to verify the validity of Bioelectrical impedance analysis (BIA) as a practical method of assessing body composition in patients with DMD and to investigate the effect of zinc supplementation on serum zinc and bone parameters in this population. Therefore, two studies were carried out: the first observational cross-sectional study including 46 patients with DMD (Study 1) and the second study with an interventional design nested in a cohort including 34 patients with DMD (Study 2). The studies were carried out at the HUOL Neurology clinic in Natal/RN. Initially, the studied population was characterized. The main finding of Study 1 was that BIA is a viable method to estimate % fat-free mass (%FFM) in children and adolescents with DMD. Among the eight predictive equations evaluated, five equations were accurate to estimate %FFM by BIA in patients with DMD, since %FFM values correlated with %FFM values determined by DXA, according to correlation tests (p<0.05). Furthermore, these values were not significantly bias, according to the Bland-Altman test (p>0.05). The main findings of Study 2 were that oral zinc supplementation increased bone mineral density (BMD) from 0.83 ± 0.05 g/cm2 to 0.84 ± 0.04 g/cm2 in those patients who had adequate BMD (p<0.05) and increased serum zinc levels from 58 ± 5 µg/dL to 74 ± 11 µg/dL in participants who had prior zinc deficiency (p<0.05). These studies will serve as a basis for the assessment of body composition using BIA in patients with DMD and for possible interventions with zinc in patients with DMD (supplemented with vitamin D and calcium) who have zinc deficiency or adequate bone density.